Oncological outcomes in extended time intervals between preoperative chemoradiotherapy with capecitabine and surgery in operable rectal adenocarcinoma - Muñoz, Miguel A.; Palacios, Manuel G.; Malca, Jenny; Mantilla, Raúl; Montenegro, Paola C.; Chavez, Ivan (Revista de Gastroenterología del Perú, 2018)
Objective: To assess whether extended time intervals (8-12, 13-20 and >20 weeks) between the end of neoadjuvant chemoradiotherapy and surgery affect overall survival, disease-free survival. Materials and methods: Retrospective study in 120 patients with rectal adenocarcinoma without evidence of metastasis (T1-4/N0-2/M0) at the time of diagnosis that underwent surgery with curative intent after neoadjuvant chemoradiotherapy with capecitabine and obtained R0 or R1 resection between January 2010 to December 2014 at the National Cancer Institute of Peru. Dates were evaluated by Kaplan-Meier method, logrank test and Cox regression analysis. Results: Of the 120 patients, 70 were women (58%). The median age was 63(26-85) years. All received neoadjuvant chemoradiotherapy. No significant difference was found between the association of the median radial (0.6, 0.7 and 0.8 cm; p=0.826) and distal edge (3.0, 3.5 and 4.0 cm; p=0.606) with time interval groups and similarly the mean resected (18.8, 19.1 and 16.0; p=0.239) and infiltrated nodules (1.05, 1.29 and 0.41); p=0.585). The median follow-up time of overall survival and desease free survival was 40 and 37 months, respectively. No significant differences were observed in overall survival (79.0%, 74.6% and 71.1%; p=0.66) and disease-free survival (73.7%, 68.1% and 73.6%; p=0.922) according to the three groups studied at the 3-year of follow-up. Conclusions: We found that widening the time intervals between the end of neoadjuvant chemoradiotherapy and surgery at 24 weeks does not affect the overall survival, disease-free survival and pathological outcomes. It allows to extend the intervals of time for future studies that finally will define the best time interval for the surgery.